MoU signing with New Era University College / Assoc Prof Dr Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2024)
The memorandum of understanding was signed between Universiti Teknologi MARA and New Era College University on May 5 2023. Both parties agreed to cooperate and encourage participation in the following activities/areas: 1. institutional exchanges between faculty and staff from each partner 2. institution; acceptance of undergraduate and graduate students of each partner institution for periods of study and/or research; 3.organization of symposia, conferences, short courses, and meetings on research issues; 4. exchange of information about developments in teaching, student development and research; 5. mutually promoting information and activities of partner universities within the MoU on their respective websites and 6. cooperation in any other areas as agreed to by the Parties from time to time.